Corticostriatal Plastic Changes in Experimental L-DOPA-Induced Dyskinesia - Veronica Ghiglieri; Vincenza Bagetta; Valentina Pendolino; Barbara Picconi; Paolo Calabresi (Parkinson's Disease)
In Parkinson’s disease (PD), alteration of dopamine- (DA-) dependent striatal functions and pulsatile stimulation of DA receptors caused by the discontinuous administration of levodopa (L-DOPA) lead to a complex cascade of events affecting the postsynaptic striatal neurons that might account for the appearance of L-DOPA-induced dyskinesia (LID). Experimental models of LID have been widely used and extensively characterized in rodents and electrophysiological studies provided remarkable insights into the inner mechanisms underlying L-DOPA-induced corticostriatal plastic changes. Here we provide an overview of recent findings that represent a further step into the comprehension of mechanisms underlying maladaptive changes of basal ganglia functions in response to L-DOPA and associated to development of LID.